The Use of Modals in Malaysian ESL Learners’ Writing - Abdul Manaf, Umi Kalthom (2007)
This research investigated Malaysian ESL learners’ use of modals in two written tasks, which were obtained from the EMAS Corpus. The aim of the study was to investigate: (1) the distribution of modals used in the students’ writing, (2) the functions depicted by the modals used, (3) if the modals used were accurate syntactically and semantically, (4) if students were using other alternatives in instances where modals were absent or inappropriately used, and (5) if students’ mastery of the use of modals and the functions in their writing reflect their ability in using modals taught to them according to those stipulated in the KBSR/KBSM syllabus (MoE, 2003). This was addressed in six research questions. The research design comprised a qualitative technique through discourse analysis supplemented with some descriptive statistics derived from a concordancer. The concordancer identified modals used by the students at all the three different levels. The research findings showed that the modals can, could and their negated forms were the modals that were most frequently used by these students. Two modals that were not stipulated in the KBSR/KBSM syllabus, would and shall, were also found in the essays. The syllabus also indicated varied meanings to the modals, but it was found that students repetitively used only a few of the same modals for these various functions. It was also found that students at the lower level were less competent in using past form modals as compared to those at the higher level. The findings also showed that students’ difficulties in constructing modal structures can be grouped into two categories: (1) modals with inaccurate verb form and (2) modals with no verb but replaced with other words/adjectives. The modals used were found to be reflective of students’ knowledge. Students were uncertain about which modals to use to express modality in their sentences and this could be seen in the inaccuracies at the syntactic and semantic levels. Malaysian English also emerged in the students’ writing. It was also found that ESL learners had adopted ways to overcome their inadequacy in the use of modals and modality of the English language by using simplification features and compensation strategies. It was concluded that there were some inadequacies in the syllabus that could have led to the problems encountered by ESL students. In order to circumvent the problematic grammatical items identified in the study, and to further improve the teaching and learning of modal auxiliary among ESL learners, several recommendations are proposed. Among them is reviewing the syllabus so that the contents of textbooks will be in line with the recommended textbooks used by students and incorporating some pedagogical aspects that will help students in acquiring and using modal verbs appropriately.